2021
DOI: 10.15446/revfacmed.v70n1.90501
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among health care workers treated at a university hospital in Bogotá D.C., Colombia. 2008-2018

Abstract: Introducción. Cada minuto tres personas mueren de tuberculosis (TB) en el mundo. El riesgo de transmisión en trabajadores de la salud es hasta 40 veces mayor que en población general. Sin embargo, en Colombia se ha dado poca importancia a esta situación. Objetivo. Describir las características demográficas y clínicas de trabajadores de la salud con TB atendidos en un hospital universitario de Bogotá D.C., Colombia, así como los hallazgos paraclínicos (de laboratorio, histológicos y radiológicos) y los principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The findings of Jurado et al 2 differ from those reported by Vargas-Restrepo, 3 who described cases of active TB between 2011 and 2017 in Colombian health care workers, finding 715 patients who mostly worked as nursing assistants and dentists (36.4%), followed by physicians (20.1%), and nurses (15.4%).…”
contrasting
confidence: 58%
See 4 more Smart Citations
“…The findings of Jurado et al 2 differ from those reported by Vargas-Restrepo, 3 who described cases of active TB between 2011 and 2017 in Colombian health care workers, finding 715 patients who mostly worked as nursing assistants and dentists (36.4%), followed by physicians (20.1%), and nurses (15.4%).…”
contrasting
confidence: 58%
“…It is striking that the study of Jurado et al 2 did not report any cases of TB in internists, pulmonologists or infectious disease specialists, which demonstrates the importance of providing adequate protection to all health care professionals, regardless of their perception of exposure to the disease or the patients they assess.…”
mentioning
confidence: 95%
See 3 more Smart Citations